Salt-Tolerant PGPR Confer Salt Tolerance to Maize Through Enhanced Soil Biological Health, Enzymatic Activities, Nutrient Uptake and Antioxidant Defense - Shabaan, Muhammad; Asghar, Hafiz Naeem; Zahir, Zahir Ahmad; Zhang, Xiu; Sardar, Muhammad Fahad; Li, Hongna (Frontiers in Microbiology, 2022)
Salt-tolerant plant growth-promoting rhizobacteria (PGPR) can improve soil enzyme activities, which are indicators of the biological health of the soil, and can overcome the nutritional imbalance in plants. A pot trial was executed to evaluate the effect of inoculation of different salt-tolerant PGPR strains in improving soil enzyme activities. Three different salinity levels (original, 5, and 10 dS m–1) were used and maize seeds were coated with the freshly prepared inocula of ten different PGPR strains. Among different strains, inoculation of SUA-14 (Acinetobacter johnsonii) caused a maximum increment in urease (1.58-fold), acid (1.38-fold), and alkaline phosphatase (3.04-fold) and dehydrogenase (72%) activities as compared to their respective uninoculated control. Acid phosphatase activities were found to be positively correlated with P contents in maize straw (r = 0.96) and grains (r = 0.94). Similarly, a positive correlation was found between alkaline phosphatase activities and P contents in straw (r = 0.77) and grains (r = 0.75). In addition, urease activities also exhibited positive correlation with N contents in maize straw (r = 0.92) and grains (r = 0.91). Moreover, inoculation of Acinetobacter johnsonii caused a significant decline in catalase (39%), superoxide dismutase (26%) activities, and malondialdehyde contents (27%). The PGPR inoculation improved the soil’s biological health and increased the uptake of essential nutrients and conferred salinity tolerance in maize. We conclude that the inoculation of salt-tolerant PGPR improves soil enzyme activities and soil biological health, overcomes nutritional imbalance, and thereby improves nutrient acquisition by the plant under salt stress.